Mathematical model of request routing in content delivery networks with guaranteed quality of service - Yevsyeyeva, O. Yu.; Khader, M. B. (Sevastopol, 2013)
The request routing in content delivery networks (CDNs) is traditionally related to choosing the appropriate mirrored server only. At the same time, the need of providing guaranteed quality of service necessitates conversion to solving of request routing on CDN together integrated with traffic routing in transport telecommunication network. The mathematical model that allows obtaining integral optimal solution of both tasks has been offered.